Pengaruh Program Gerakan Literasi Sekolah Terhadap Minat Baca Dan Hasil Belajar Bahasa Indonesia Siswa Kelas V SDN 9 Mataram - Nurulaili, Annisaa; Gunayasa, Ida Bagus Kade; Istiningsih, Siti (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
This study aims to determine the effect of the School Literacy Movement Program on reading interest and Indonesian language learning outcomes in fifth grade students of SDN 9 Mataram. The type of research used in this research is correlational research that uses the ex post facto method. The population of this study was the fifth grade students of SDN 9 Mataram, totaling 35 students. In determining the sample, it is done by using the Saturated Sample Technique. This technique is used because, all the population will be used as a sample. Data on the school literacy movement program and reading interest were collected using a questionnaire and Indonesian language learning outcomes using the even semester report cards for the 2020/2021 academic year. Data were analyzed using simple correlation analysis and simple regression analysis assisted by SPSS version 21.0 for windows. The results of this study indicate that: first, there is a significant influence between the school literacy movement program on the reading interest of the fifth grade students of SDN 9 Mataram. Second, there is a significant influence between the school literacy movement program on the Indonesian language learning outcomes of fifth grade students at SDN 9 Mataram. Keywords: School Literacy Movement, Reading Interest, Learning Outcomes.